Teamwork Development across the Curriculum for Information Technology Students at Liepāja University: Processes, Outcomes and Lessons Learned - Tomsons, Dzintars; Jansone, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Teamwork skills are key feature for Information Technology (IT) specialists. The university IT curriculum contains both IT specific courses, and comprehensive courses. Due to limited amount of the learning courses and efficient achievement of learning goals, it is necessary to look for opportunities to integrate activities developing social and communication skills courses into IT specific courses. Managing the teamwork that is close to practice, it is necessary to solve the problems of teaching and learning organisation, and assessment of individual learning outcomes and competences. In Liepāja University, the student teamwork has been managed for several years as integral part of Software Engineering courses and study projects. The course management system Moodle has been used in learning process providing possibilities to evaluate both assignments submitted by students and their learning behaviour. The current paper describes and analyses the experience of academic staff of Liepāja University.